(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In this article the mountain rock Flicker is the highest loaded and bulk of the drilling equipment. A large part of the efficiency of drilling equipment is due to the work of mountain rock flicker tools, and it has been found that many factors influence the work of a mountain rock flicker tool